COVID-19 and Digitization of SMEs: The Impact and Way Forward - Ghimire, Aarashi; Jaiswal, Bikash; Shrestha, Jasmine; Shrestha, Kripa; Shrestha, Souhard (New Perspective: Journal of Business and Economics, 2023)
The Covid-19 pandemic has brought significant changes to the global economy, particularly in terms of digitization. This study aims to examine the role of digitization in helping small and medium-sized enterprises (SMEs) survive during the pandemic in Nepal and assess its sustainability for the future. The sample for this study consists of 52 SMEs from various industries such as clothing, food, and retail businesses. A quantitative research approach is employed to analyze the data. The findings of this study indicate that there was little to no change in the adoption of digitalization among SMEs before and after the crisis. This suggests that the level of digitization in SMEs remains relatively unchanged in the post-Covid-19 period. However, in terms of sustainability, the study reveals that SMEs need to undergo digital transformation to ensure their long-term viability. This finding aligns with previous research that emphasizes the importance of digital technologies for SMEs in emerging markets. The literature review supports the notion that social media advertising can increase brand loyalty and provide opportunities for direct interaction with potential customers. Additionally, studies have shown that social media influencers have a positive impact on the buying decision process of customers. Furthermore, research has demonstrated that social media marketing influences consumer decision-making processes. It underscores the potential benefits of digitization in terms of survival and sustainability. The findings suggest that SMEs should prioritize digitalization efforts to adapt to the changing business landscape and enhance their competitiveness. In conclusion, this study emphasizes the importance of digitization for SMEs in Nepal, particularly in the context of the Covid-19 pandemic. The findings indicate the need for SMEs to embrace digital transformation to ensure their long-term viability.